Preparation method and application of magnetic recoverable composite photocatalyst with mosaic structure

A magnetic recyclable composite photocatalyst with an inlaid structure addresses agglomeration issues by uniformly embedding the ferroelectric phase, enhancing both magnetic recovery and piezoelectric performance in a stable, low-energy process.

CN119215920APending Publication Date: 2024-12-31HARBIN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411350517.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The excessive addition of magnetic phase in existing magnetic composite catalyst powders leads to agglomeration, causing leakage currents and deteriorating ferroelectric polarization, thus affecting piezoelectric photocatalytic performance.

Method used

A magnetic recyclable composite photocatalyst with an inlaid structure, comprising aBi2WO6 inlaid with bBFe2O4, where a and b are within specific ratios, is prepared using a sol-gel method to ensure the ferroelectric catalyst phase is uniformly embedded, preventing agglomeration and maintaining polarization strength.

Benefits of technology

The inlaid structure enhances magnetic recovery performance while improving piezoelectric catalytic performance, with a stable and low-energy preparation process that avoids agglomeration and leakage currents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215920A_ABST
    Figure CN119215920A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a magnetic recoverable composite photocatalyst with a mosaic structure, and relates to a preparation method and application of a photocatalyst. The invention aims to solve the problem that the catalytic performance is influenced by agglomeration caused by excessive adding content of a magnetic phase in the existing multiphase catalyst powder with magnetism. The invention relates to a magnetic recoverable composite photocatalyst with an inlaid structure. A ferroelectric catalyst phase bBFe2O4 is inlaid in a multiphase catalyst phase aBi2WO6, and B is a cobalt element or a nickel element. The method comprises the following steps: 1, preparing sol A; 2, preparing sol B; 3, preparing sol C; 4, preparing sol D; 5, preparing mixed sol E; 6, drying; 7, carbonizing; and 8, calcining. A mosaic structure is designed, that is, a ferroelectric catalyst phase is uniformly inlaid in a multiphase catalyst phase, so that the ferroelectric catalyst phase cannot be agglomerated on a crystal boundary, current leakage after agglomeration of the ferroelectric catalyst phase is avoided, and the structure can effectively improve the degradation performance of the piezoelectric photocatalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a photocatalyst. Background Art

[0002] As a technology that directly utilizes the mechanical energy generated by solar energy and water flow to degrade target pollutants, piezoelectric photocatalysis has the advantages of being environmentally friendly, low in preparation cost, high in performance, pollution-free in products, and high in degradation rate. It is currently widely used in sewage treatment, aquaculture, indoor cleaning and other fields. However, after the piezoelectric photocatalyst undergoes a catalytic reaction, there has always been a problem of separating it from the treatment environment. Adding magnetic materials to the photocatalyst and using an external magnetic field to recover the photocatalyst is a new idea for effectively separating and recovering the photocatalyst. However, in order to show higher macroscopic magnetism, the addition of a large amount of magnetic material will produce agglomeration, leading to serious leakage current, thereby causing the destruction of ferroelectric polarization, seriously affecting the piezoelectric photocatalytic performance. For composite materials, the current composite method cannot solve the agglomeration behavior after the addition of a large amount of the second phase. Summary of the invention

[0003] The purpose of the present invention is to solve the problem that excessive addition of magnetic phase in existing magnetic composite catalyst powder leads to agglomeration, thereby affecting the catalytic performance, and to provide a preparation method and application of a multiferroic composite ceramic with an inlaid structure.

[0004] A magnetic recyclable composite photocatalyst with an inlaid structure is a composite catalyst phase aBi2WO6 inlaid with an iron electrocatalyst phase bBFe2O4, wherein a is the amount of Bi2WO6, b is the amount of BFe2O4, and 0.5≤a≤0.95, 0.05≤b≤0.5, a+b=1, B is a cobalt element or a nickel element, Fe is an iron element, O is an oxygen element, Bi is a bismuth element, and W is a tungsten element; the preparation method is specifically completed according to the following steps:

[0005] 1. Preparation of Sol A:

[0006] ①, adding bismuth salt and citric acid into deionized water, heating and stirring until completely dissolved, to obtain a citric acid solution of bismuth salt;

[0007] The bismuth salt described in step 1① is bismuth subnitrate or bismuth acetate;

[0008] The molar ratio of citric acid to bismuth salt in step 1① is 2:1;

[0009] ②, add a complexing agent to the citric acid solution of bismuth salt, then add ammonia water to adjust the pH value of the system to 6-7, stir at 70-80°C for a period of time to obtain sol A;

[0010] The complexing agent described in step 1② is ethylenediaminetetraacetic acid or ethylene glycol;

[0011] 2. Preparation of Sol B:

[0012] ①. Add tungsten salt and citric acid into deionized water, heat and stir until completely dissolved to obtain tungsten salt citric acid solution;

[0013] The tungsten salt described in step 2① is ammonium paratungstate;

[0014] The molar ratio of citric acid to tungsten salt in step 2① is 2:1;

[0015] ②, add complexing agent to the citric acid solution of tungsten salt, then add ammonia water to adjust the pH value of the system to 6-7, stir at 70℃-80℃ for a period of time to obtain sol B;

[0016] The complexing agent described in step 2② is ethylenediaminetetraacetic acid or ethylene glycol;

[0017] 3. Preparation of Sol C:

[0018] Sol A and Sol B are fully mixed, and then heated and stirred for a period of time to obtain Sol C;

[0019] The molar ratio of sol A to sol B described in step 3 is 1:2;

[0020] 4. Preparation of Sol D:

[0021] ①. Weigh cobalt salt or nickel salt as raw material 1; weigh ferric nitrate as raw material 2; add raw material 1, raw material 2 and citric acid into deionized water, heat and stir until completely dissolved, to obtain a citric acid solution of the raw materials;

[0022] The molar ratio of raw material 1 and raw material 2 described in step 4① is 1:2;

[0023] The molar ratio of the mass of citric acid described in step 4① to raw material 1 is 2:1;

[0024] ②, add a complexing agent to the citric acid solution of the raw material, then add ammonia water to adjust the pH value of the system to 6-7, stir at room temperature for a period of time to obtain sol D;

[0025] The complexing agent described in step 4② is ethylenediaminetetraacetic acid or ethylene glycol; the complexing agent described in step 1②, step 2② and step 3 is the same substance;

[0026] 5. Preparation of mixed sol E:

[0027] Sol D and Sol C are fully mixed, heated and stirred for a period of time to obtain mixed sol E;

[0028] The molar ratio of sol C and sol D in step 5 is a:b, wherein 0.5≤a≤0.95, 0.05≤b≤0.5, a+b=1;

[0029] 6. Drying:

[0030] The mixed sol E was placed in a dust-free environment and kept at 80°C for a period of time to obtain a mixed xerogel;

[0031] 7. Carbonization:

[0032] The mixed xerogel obtained in step 6 is kept at 180-200° C. for a period of time to obtain a foamy black xerogel;

[0033] 8. Calcination:

[0034] The foamy black dry gel obtained in step seven is heated from room temperature to 100°C to 300°C at a heating rate of 1°C / min to 5°C / min, and kept at this temperature for 30min to 1h; then the temperature is increased to 550°C to 750°C at a heating rate of 5°C / min to 15°C / min, and kept at this temperature for 1h to 2h, and then cooled to room temperature in the furnace to obtain a magnetic recyclable composite photocatalyst with a mosaic structure.

[0035] A magnetic recyclable composite photocatalyst with mosaic structure for degradation of rhodamine B.

[0036] Advantages of the present invention:

[0037] 1. In the magnetic recyclable composite photocatalyst with a mosaic structure prepared by the present invention, almost all the ferroelectric catalyst phase is embedded in the composite catalyst phase grains;

[0038] Second, the present invention does not destroy the internal polarization electric field strength of the piezoelectric catalyst due to the addition of the magnetic phase, and the piezoelectric catalytic performance is improved while having the magnetic recovery performance;

[0039] 3. The sol-gel method used in the present invention has a stable process, a short cycle, and low energy consumption, and the preparation process does not involve high-pressure reaction, and has a high safety factor;

[0040] Fourth, the present invention designs an embedded structure, that is, the ferroelectric catalyst phase is uniformly embedded in the complex catalyst phase, so that it cannot agglomerate on the grain boundary, avoiding leakage current after agglomeration. This structure can effectively improve the degradation performance of the piezoelectric photocatalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The dark field phase of the magnetic recyclable composite photocatalyst with mosaic structure prepared in Example 1;

[0042] Figure 2The hysteresis loop diagram of the magnetic recyclable composite photocatalyst with a mosaic structure prepared in Example 1;

[0043] Figure 3 This is a photo of the magnetic recyclable composite photocatalyst with a mosaic structure prepared in Example 2 dispersed in deionized water and after a magnet is applied;

[0044] Figure 4 This is a graph showing the degradation efficiency of Rhodamine B using Bi2WO6 and the magnetic recyclable composite photocatalysts with a mosaic structure prepared in Examples 1 to 3. In the graph, BWO is the Bi2WO6 prepared in Control Example 1, 5CFO is the magnetic recyclable composite photocatalyst with a mosaic structure prepared in Example 2, 10CFO is the magnetic recyclable composite photocatalyst with a mosaic structure prepared in Example 1, and 20CFO is the magnetic recyclable composite photocatalyst with a mosaic structure prepared in Example 3. DETAILED DESCRIPTION

[0045] Specific implementation method 1: This implementation method is a magnetic recyclable composite photocatalyst with an inlaid structure, in which a ferroelectric catalyst phase bBFe2O4 is inlaid in a complex catalyst phase aBi2WO6, wherein a is the amount of Bi2WO6, b is the amount of BFe2O4, and 0.5≤a≤0.95, 0.05≤b≤0.5, a+b=1, B is a cobalt element or a nickel element, Fe is an iron element, O is an oxygen element, Bi is a bismuth element, and W is a tungsten element; the preparation method is specifically completed according to the following steps:

[0046] 1. Preparation of Sol A:

[0047] ①, adding bismuth salt and citric acid into deionized water, heating and stirring until completely dissolved, to obtain a citric acid solution of bismuth salt;

[0048] The bismuth salt described in step 1① is bismuth subnitrate or bismuth acetate;

[0049] The molar ratio of citric acid to bismuth salt in step 1① is 2:1;

[0050] ②, add a complexing agent to the citric acid solution of bismuth salt, then add ammonia water to adjust the pH value of the system to 6-7, stir at 70-80°C for a period of time to obtain sol A;

[0051] The complexing agent described in step 1② is ethylenediaminetetraacetic acid or ethylene glycol;

[0052] 2. Preparation of Sol B:

[0053] ①. Add tungsten salt and citric acid into deionized water, heat and stir until completely dissolved to obtain tungsten salt citric acid solution;

[0054] The tungsten salt described in step 2① is ammonium paratungstate;

[0055] The molar ratio of citric acid to tungsten salt in step 2① is 2:1;

[0056] ②, add complexing agent to the citric acid solution of tungsten salt, then add ammonia water to adjust the pH value of the system to 6-7, stir at 70℃-80℃ for a period of time to obtain sol B;

[0057] The complexing agent described in step 2② is ethylenediaminetetraacetic acid or ethylene glycol;

[0058] 3. Preparation of Sol C:

[0059] Sol A and Sol B are fully mixed, and then heated and stirred for a period of time to obtain Sol C;

[0060] The molar ratio of sol A to sol B described in step 3 is 1:2;

[0061] 4. Preparation of Sol D:

[0062] ①. Weigh cobalt salt or nickel salt as raw material 1; weigh ferric nitrate as raw material 2; add raw material 1, raw material 2 and citric acid into deionized water, heat and stir until completely dissolved, to obtain a citric acid solution of the raw materials;

[0063] The molar ratio of raw material 1 and raw material 2 described in step 4① is 1:2;

[0064] The molar ratio of the mass of citric acid described in step 4① to raw material 1 is 2:1;

[0065] ②, add a complexing agent to the citric acid solution of the raw material, then add ammonia water to adjust the pH value of the system to 6-7, stir at room temperature for a period of time to obtain sol D;

[0066] The complexing agent described in step 4② is ethylenediaminetetraacetic acid or ethylene glycol; the complexing agent described in step 1②, step 2② and step 3 is the same substance;

[0067] 5. Preparation of mixed sol E:

[0068] Sol D and Sol C are fully mixed, heated and stirred for a period of time to obtain mixed sol E;

[0069] The molar ratio of sol C and sol D in step 5 is a:b, wherein 0.5≤a≤0.95, 0.05≤b≤0.5, a+b=1;

[0070] 6. Drying:

[0071] The mixed sol E was placed in a dust-free environment and kept at 80°C for a period of time to obtain a mixed xerogel;

[0072] 7. Carbonization:

[0073] The mixed xerogel obtained in step 6 is kept at 180-200° C. for a period of time to obtain a foamy black xerogel;

[0074] 8. Calcination:

[0075] The foamy black dry gel obtained in step seven is heated from room temperature to 100°C to 300°C at a heating rate of 1°C / min to 5°C / min, and kept at this temperature for 30min to 1h; then the temperature is increased to 550°C to 750°C at a heating rate of 5°C / min to 15°C / min, and kept at this temperature for 1h to 2h, and then cooled to room temperature in the furnace to obtain a magnetic recyclable composite photocatalyst with a mosaic structure.

[0076] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that: the mass ratio of citric acid to deionized water in step 1① is 1g:(15mL-25mL); the temperature of heating and stirring in step 1① is 70℃-80℃, and the stirring speed is 100r / min-300r / min. The other steps are the same as those in specific embodiment 1.

[0077] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the molar ratio of the complexing agent described in step one ② to the citric acid described in step one ① is (1.0-1.5):1; the stirring speed in step one ② is 100r / min-300r / min, and the stirring time is 60min-75min; the mass ratio of the citric acid described in step two ① to the volume ratio of deionized water is 1g:(15mL-25mL); the temperature of the heating and stirring described in step two ① is 70℃-80℃, and the stirring speed is 100r / min-300r / min. The other steps are the same as specific implementation method one or two.

[0078] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the molar ratio of the complexing agent described in step 2 ② to the citric acid described in step 2 ① is (1.0-1.5):1; the stirring speed in step 2 ② is 100r / min-300r / min, and the stirring time is 60min-75min; the heating stirring temperature described in step 3 is 70℃-80℃, the stirring speed is 100r / min-300r / min, and the stirring time is 60min-75min. The other steps are the same as specific embodiments 1 to 3.

[0079] Specific implementation mode five: This implementation mode is different from specific implementation modes one to four in that: the cobalt salt described in step four ① is cobalt nitrate or cobalt acetate; the nickel salt described in step four ① is nickel nitrate or nickel acetate; the mass ratio of citric acid described in step four ① to deionized water is 1g:(15mL~25mL); the heating and stirring temperature described in step four ① is 70℃~80℃, and the stirring speed is 100r / min~300r / min.

[0080] The other steps are the same as those in Specific Embodiments 1 to 4.

[0081] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that the molar ratio of the complexing agent described in step 4 ② to the citric acid described in step 4 ① is (1.0 to 1.5):1; the stirring speed described in step 4 ② is 100 r / min to 300 r / min, and the stirring time is 60 min to 75 min. The other steps are the same as those of specific embodiments 1 to 5.

[0082] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the heating and stirring temperature in step 5 is 70°C to 80°C, the stirring speed is 100r / min to 300r / min, and the stirring time is 60min to 75min. The other steps are the same as those in specific embodiments 1 to 6.

[0083] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the time of keeping the temperature at 80° C. in step 6 is 24 to 36 hours. The other steps are the same as those of specific embodiments 1 to 7.

[0084] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the time of keeping the temperature at 180-200° C. in step 7 is 60-70 minutes. The other steps are the same as those of specific embodiments 1 to 8.

[0085] Specific embodiment ten: This embodiment is a magnetic recyclable composite photocatalyst with a mosaic structure for degrading rhodamine B.

[0086] The following examples are used to verify the beneficial effects of the present invention:

[0087] Example 1: A magnetic recyclable composite photocatalyst with an inlaid structure is a composite catalyst phase aBi2WO6 inlaid with a ferroelectric catalyst phase bBFe2O4, wherein a is the amount of Bi2WO6, b is the amount of CoFe2O4, and a=0.90, b=0.10, a+b=1; the preparation method is specifically completed according to the following steps:

[0088] 1. Preparation of Sol A:

[0089] ①, adding bismuth salt and citric acid into deionized water, heating and stirring at 80°C and a stirring speed of 200 r / min until completely dissolved, to obtain a citric acid solution of bismuth salt;

[0090] The bismuth salt described in step 1① is bismuth subnitrate;

[0091] The molar ratio of citric acid to bismuth salt in step 1① is 2:1;

[0092] The mass ratio of citric acid described in step 1① to deionized water is 1g:20mL;

[0093] ②, add a complexing agent to the citric acid solution of bismuth salt, then add ammonia water to adjust the pH value of the system to 7, and continue stirring at 80° C. at a stirring speed of 200 r / min for 65 min to obtain sol A;

[0094] The complexing agent described in step 1② is ethylenediaminetetraacetic acid;

[0095] The molar ratio of the complexing agent described in step 1 ② to the citric acid described in step 1 ① is 1.5:1;

[0096] 2. Preparation of Sol B:

[0097] ①. Add tungsten salt and citric acid into deionized water, heat and stir at 80℃ and stirring speed of 200r / min until completely dissolved to obtain tungsten salt citric acid solution;

[0098] The tungsten salt described in step 2① is ammonium paratungstate;

[0099] The molar ratio of citric acid to tungsten salt in step 2① is 2:1;

[0100] The mass ratio of citric acid to deionized water described in step 2① is 1g:20mL;

[0101] ②, add a complexing agent to the citric acid solution of tungsten salt, then add ammonia water to adjust the pH value of the system to 7, and continue stirring at 80°C at a stirring speed of 200r / min for 65min to obtain Sol B;

[0102] The complexing agent described in step 2② is ethylenediaminetetraacetic acid;

[0103] The molar ratio of the complexing agent described in step 2② to the citric acid described in step 2① is 1.5:1;

[0104] 3. Preparation of Sol C:

[0105] Sol A and Sol B were fully mixed, and then stirred at 80°C and a stirring speed of 200 r / min for 70 min to obtain Sol C;

[0106] The molar ratio of sol A to sol B described in step 3 is 1:2;

[0107] 4. Preparation of Sol D:

[0108] ①. Weigh cobalt salt or nickel salt as raw material 1; weigh ferric nitrate as raw material 2; add raw material 1, raw material 2 and citric acid into deionized water, heat and stir at 80°C and a stirring speed of 200 r / min until completely dissolved, to obtain a citric acid solution of the raw materials;

[0109] The cobalt salt described in step 4① is cobalt nitrate;

[0110] The molar ratio of raw material 1 and raw material 2 described in step 4① is 1:2;

[0111] The molar ratio of the mass of citric acid described in step 4① to raw material 1 is 2:1;

[0112] The mass ratio of citric acid to deionized water described in step 4① is 1g:20mL;

[0113] ②, add a complexing agent to the citric acid solution of the raw material, then add ammonia water to adjust the pH value of the system to 7, and continue stirring at a stirring speed of 200 r / min at room temperature for 70 minutes to obtain sol D;

[0114] The complexing agent described in step 4② is ethylenediaminetetraacetic acid;

[0115] The molar ratio of the complexing agent described in step 4② to the citric acid described in step 4① is 1.5:1;

[0116] 5. Preparation of mixed sol E:

[0117] Sol D and Sol C were fully mixed, and then heated and stirred at 80°C and a stirring speed of 200 r / min for a period of time to obtain a mixed sol E;

[0118] The molar ratio of Sol C and Sol D described in step 5 is a:b, a=0.90, b=0.10;

[0119] 6. Drying:

[0120] The mixed sol E was placed in a dust-free environment and kept at 80°C for 24 hours to obtain a mixed xerogel;

[0121] 7. Carbonization:

[0122] The mixed xerogel obtained in step 6 was kept at 180°C for 60 min to obtain a foamy black xerogel;

[0123] 8. Calcination:

[0124] The foamy black dry gel obtained in step seven is heated from room temperature to 300°C at a heating rate of 1°C / min, and kept at this temperature for 1 hour; then heated to 600°C at a heating rate of 5°C / min, and kept at this temperature for 1 hour, and cooled to room temperature in the furnace to obtain a multiferroic composite ceramic with an inlaid structure (denoted as 10CFO).

[0125] Example 2: The difference between this example and Example 1 is that: a magnetic recyclable composite photocatalyst with an inlaid structure is a composite catalyst phase aBi2WO6 inlaid with a ferroelectric catalyst phase bBFe2O4, wherein a is the amount of Bi2WO6, b is the amount of CoFe2O4, and a=0.95, b=0.05, a+b=1; the molar ratio of sol C and sol D described in step 5 is a:b, a=0.95, b=0.05; in step 8, a multiferroic composite ceramic with an inlaid structure (referred to as 5CFO) is obtained. The other steps and parameters are the same as those in Example 1.

[0126] Example 3: The difference between this example and Example 1 is that: a magnetic recyclable composite photocatalyst with an inlaid structure is a composite catalyst phase aBi2WO6 inlaid with a ferroelectric catalyst phase bBFe2O4, wherein a is the amount of Bi2WO6, b is the amount of CoFe2O4, and a=0.8, b=0.2, a+b=1; the molar ratio of sol C and sol D described in step 5 is a:b, a=0.8, b=0.2; and a multiferroic composite ceramic (referred to as 20CFO) with an inlaid structure is obtained in step 8. The other steps and parameters are the same as those in Example 1.

[0127] Comparative Example 1: The preparation method of Bi2WO6 is specifically completed according to the following steps:

[0128] 1. Preparation of Sol A:

[0129] ①, adding bismuth salt and citric acid into deionized water, heating and stirring at 80°C and a stirring speed of 200 r / min until completely dissolved, to obtain a citric acid solution of bismuth salt;

[0130] The bismuth salt described in step 1① is bismuth subnitrate;

[0131] The molar ratio of citric acid to bismuth salt in step 1① is 2:1;

[0132] The mass ratio of citric acid described in step 1① to deionized water is 1g:20mL;

[0133] ②, add a complexing agent to the citric acid solution of bismuth salt, then add ammonia water to adjust the pH value of the system to 7, and continue stirring at 80° C. at a stirring speed of 200 r / min for 65 min to obtain sol A;

[0134] The complexing agent described in step 1② is ethylenediaminetetraacetic acid;

[0135] The molar ratio of the complexing agent described in step 1 ② to the citric acid described in step 1 ① is 1.5:1;

[0136] 2. Preparation of Sol B:

[0137] ①. Add tungsten salt and citric acid into deionized water, heat and stir at 80℃ and stirring speed of 200r / min until completely dissolved to obtain tungsten salt citric acid solution;

[0138] The tungsten salt described in step 2① is ammonium paratungstate;

[0139] The molar ratio of citric acid to tungsten salt in step 2① is 2:1;

[0140] The mass ratio of citric acid to deionized water described in step 2① is 1g:20mL;

[0141] ②, add a complexing agent to the citric acid solution of tungsten salt, then add ammonia water to adjust the pH value of the system to 7, and continue stirring at 80°C at a stirring speed of 200r / min for 65min to obtain Sol B;

[0142] The complexing agent described in step 2② is ethylenediaminetetraacetic acid;

[0143] The molar ratio of the complexing agent described in step 2② to the citric acid described in step 2① is 1.5:1;

[0144] 3. Preparation of Sol C:

[0145] Sol A and Sol B were fully mixed, and then stirred at 80°C and a stirring speed of 200 r / min for 70 min to obtain Sol C;

[0146] The molar ratio of sol A to sol B described in step 3 is 1:2;

[0147] 4. Drying:

[0148] Sol C was placed in a dust-free environment and kept at 80°C for 24 hours to obtain a mixed xerogel;

[0149] 5. Carbonization:

[0150] The mixed xerogel obtained in step 4 is kept at 180° C. for 60 min to obtain a carbonized gel;

[0151] 6. Calcination:

[0152] The carbonized gel obtained in step five is heated from room temperature to 300°C at a heating rate of 1°C / min, and kept at this temperature for 1 hour; then heated to 600°C at a heating rate of 5°C / min, and kept at this temperature for 1 hour, and then cooled to room temperature in the furnace to obtain Bi2WO6.

[0153] Figure 1 The dark field phase of the magnetic recyclable composite photocatalyst with mosaic structure prepared in Example 1;

[0154] Figure 1 The grain morphology of the multiferroic composite ceramic with mosaic structure prepared in Example 1 is shown. There are two types of grains, namely small square grains distributed inside large equiaxed grains. In addition, it is shown that the two grains present different colors. The light-colored small square grains are evenly dispersed in the large dark equiaxed crystals, and the light-colored small grains are completely embedded in the dark large equiaxed crystals to form a mosaic structure. The light-colored grains are ferromagnetic phase CoFe2O4 embedded in the photocatalytic phase Bi2WO6; the black CoFe2O4 crystals are dispersed inside the light-colored Bi2WO6 grains to present the expected mosaic structure.

[0155] Figure 2 The hysteresis loop diagram of the magnetic recyclable composite photocatalyst with a mosaic structure prepared in Example 1;

[0156] from Figure 2 It can be seen that the magnetic recyclable composite photocatalyst with a mosaic structure prepared in Example 1 has good magnetic properties.

[0157] 1 g of the multiferroic composite ceramic with mosaic structure prepared in Example 2 was placed in 5 mL of deionized water, and after uniform ultrasonication, the composite ceramic powder was collected by applying a magnet outside the container. Figure 3 As shown;

[0158] Figure 3 This is a photo of the magnetic recyclable composite photocatalyst with a mosaic structure prepared in Example 2 dispersed in deionized water and after a magnet is applied;

[0159] Figure 3 The results show that 5 mol% CoFe2O4 composite photocatalyst powder is dispersed in a solution and then left to stand for 2 minutes after an external magnetic field is added. Therefore, it can be concluded that the composite powder has good magnetic recovery ability at 10 mol% and 20 mol% CoFe2O4 addition levels.

[0160] Rhodamine B (RhB) was used as a pollutant to evaluate the photocatalytic activity of the magnetic recyclable composite photocatalyst with mosaic structure prepared in Examples 1 to 3 as a photocatalyst. During the photodegradation process, 20 mg of Bi2WO6 prepared in Control Example 1 and 20 mg of the magnetic recyclable composite photocatalyst with mosaic structure prepared in Examples 1 to 3 were dispersed in a 150 mL beaker of Rhodamine B solution (RhB concentration was 1×10 -5 M). Before the photocatalytic reaction, the suspension was stirred in the dark for 45 minutes to reach adsorption-desorption equilibrium. The suspension was then exposed to the light of a 300W xenon lamp (simulating sunlight), coupled with a 450W ultrasound machine (simulating river water flow) and continuous stirring. After irradiation every 15 minutes, about 3mL of the suspension was extracted and the photocatalyst was removed by high-speed centrifugation. The concentration of RhB was determined by a UV-visible spectrophotometer at 554nm. Each data point was repeated three times, and the average value was used for analysis. See Figure 4 As shown;

[0161] Figure 4 This is a graph of the degradation efficiency of Rhodamine B using Bi2WO6 and the magnetic recyclable composite photocatalyst with a mosaic structure prepared in Examples 1 to 3, in which BWO is Bi2WO6 prepared in Control Example 1, 5CFO is the magnetic recyclable composite photocatalyst with a mosaic structure prepared in Example 2, 10CFO is the magnetic recyclable composite photocatalyst with a mosaic structure prepared in Example 1, and 20CFO is the magnetic recyclable composite photocatalyst with a mosaic structure prepared in Example 3;

[0162] The experimental results show that the addition of magnetic recyclable composite photocatalyst with mosaic structure has better piezoelectric photocatalytic performance, and the catalytic efficiency is improved compared with pure phase catalyst. Under the condition of ultrasound assistance, the degradation rate of Bi2WO6 is 52% after 75 minutes of light irradiation reaction, the degradation rate of composite photocatalyst is 78% at 5mol% CoFe2O4 addition, 95% at 10mol% CoFe2O4 addition, and 58% at 20mol% CoFe2O4 addition. The composite photocatalyst with 10mol% CoFe2O4 addition shows the best photocatalytic degradation performance, and its catalytic degradation rate constant for rhodamine B reaches 0.04023 / min, which is higher than most of the current bismuth tungstate-based photocatalysts. Compared with the existing composite powder with the same content of magnetic material added without mosaic structure (0.02779 / min), it can effectively improve the piezoelectric photocatalytic performance of the photocatalyst and solve the contradiction between magnetic phase addition and piezoelectric polarization in piezoelectric photocatalysts.

Claims

1. A method for preparing a magnetic recyclable composite photocatalyst with a mosaic structure, characterized in that The magnetic recyclable composite photocatalyst with an inlaid structure is a composite catalyst phase aBi2WO6 inlaid with an iron electrocatalyst phase bBFe2O4, wherein a is the amount of Bi2WO6, b is the amount of BFe2O4, and 0.5≤a≤0.95, 0.05≤b≤0.5, a+b=1, B is a cobalt element or a nickel element, Fe is an iron element, O is an oxygen element, Bi is a bismuth element, and W is a tungsten element; the preparation method is specifically completed according to the following steps:

1. Preparation of Sol A: ①, adding bismuth salt and citric acid into deionized water, heating and stirring until completely dissolved, to obtain a citric acid solution of bismuth salt; The bismuth salt described in step 1① is bismuth subnitrate or bismuth acetate; The molar ratio of citric acid to bismuth salt in step 1① is 2:1; ②, add a complexing agent to the citric acid solution of bismuth salt, then add ammonia water to adjust the pH value of the system to 6-7, stir at 70-80°C for a period of time to obtain sol A; The complexing agent described in step 1② is ethylenediaminetetraacetic acid or ethylene glycol; 2. Preparation of Sol B: ①. Add tungsten salt and citric acid into deionized water, heat and stir until completely dissolved to obtain tungsten salt citric acid solution; The tungsten salt described in step 2① is ammonium paratungstate; The molar ratio of citric acid to tungsten salt in step 2① is 2:1; ②, add complexing agent to the citric acid solution of tungsten salt, then add ammonia water to adjust the pH value of the system to 6-7, stir at 70℃-80℃ for a period of time to obtain sol B; The complexing agent described in step 2② is ethylenediaminetetraacetic acid or ethylene glycol; 3. Preparation of Sol C: Sol A and Sol B are fully mixed, and then heated and stirred for a period of time to obtain Sol C; The molar ratio of sol A to sol B described in step 3 is 1:2; 4. Preparation of Sol D: ①. Weigh cobalt salt or nickel salt as raw material 1; weigh ferric nitrate as raw material 2; add raw material 1, raw material 2 and citric acid into deionized water, heat and stir until completely dissolved, to obtain a citric acid solution of the raw materials; The molar ratio of raw material 1 and raw material 2 described in step 4① is 1:2; The molar ratio of the mass of citric acid described in step 4① to raw material 1 is 2:1; ②, add a complexing agent to the citric acid solution of the raw material, then add ammonia water to adjust the pH value of the system to 6-7, stir at room temperature for a period of time to obtain sol D; The complexing agent described in step 4② is ethylenediaminetetraacetic acid or ethylene glycol; the complexing agent described in step 1②, step 2② and step 3 is the same substance; 5. Preparation of mixed sol E: Sol D and Sol C are fully mixed, heated and stirred for a period of time to obtain mixed sol E; The molar ratio of sol C and sol D in step 5 is a:b, wherein 0.5≤a≤0.95, 0.05≤b≤0.5, a+b=1; 6. Drying: The mixed sol E was placed in a dust-free environment and kept at 80°C for a period of time to obtain a mixed xerogel; 7. Carbonization: The mixed xerogel obtained in step 6 is kept at 180-200° C. for a period of time to obtain a foamy black xerogel; 8. Calcination: The foamy black dry gel obtained in step seven is heated from room temperature to 100°C to 300°C at a heating rate of 1°C / min to 5°C / min, and kept at this temperature for 30min to 1h; then the temperature is increased to 550°C to 750°C at a heating rate of 5°C / min to 15°C / min, and kept at this temperature for 1h to 2h, and then cooled to room temperature in the furnace to obtain a magnetic recyclable composite photocatalyst with a mosaic structure.

2. The method for preparing a magnetic recyclable composite photocatalyst with a mosaic structure according to claim 1, characterized in that The mass ratio of the citric acid described in step 1① to the volume ratio of deionized water is 1g:(15mL~25mL); the temperature of the heating and stirring described in step 1① is 70℃~80℃, and the stirring speed is 100r / min~300r / min.

3. The method for preparing a magnetic recyclable composite photocatalyst with a mosaic structure according to claim 1, characterized in that The molar ratio of the complexing agent described in step 1 ② to the citric acid described in step 1 ① is (1.0-1.5):1; the stirring speed in step 1 ② is 100 r / min-300 r / min, and the stirring time is 60 min-75 min; the volume ratio of the mass of the citric acid described in step 2 ① to deionized water is 1 g:(15 mL-25 mL); the heating and stirring temperature described in step 2 ① is 70° C.-80° C., and the stirring speed is 100 r / min-300 r / min.

4. The method for preparing a magnetic recyclable composite photocatalyst with a mosaic structure according to claim 1, characterized in that The molar ratio of the complexing agent described in step 2② to the citric acid described in step 2① is (1.0-1.5):1; the stirring speed in step 2② is 100r / min-300r / min, and the stirring time is 60min-75min; the heating and stirring temperature described in step 3 is 70℃-80℃, the stirring speed is 100r / min-300r / min, and the stirring time is 60min-75min.

5. The method for preparing a magnetic recyclable composite photocatalyst with a mosaic structure according to claim 1, characterized in that The cobalt salt described in step 4① is cobalt nitrate or cobalt acetate; the nickel salt described in step 4① is nickel nitrate or nickel acetate; the volume ratio of the mass of citric acid described in step 4① to deionized water is 1g:(15mL~25mL); the temperature of heating and stirring described in step 4① is 70℃~80℃, and the stirring speed is 100r / min~300r / min.

6. The method for preparing a magnetic recyclable composite photocatalyst with a mosaic structure according to claim 1, characterized in that The molar ratio of the complexing agent described in step 4 ② to the citric acid described in step 4 ① is (1.0-1.5):1; the stirring speed described in step 4 ② is 100r / min-300r / min, and the stirring time is 60min-75min.

7. The method for preparing a magnetic recyclable composite photocatalyst with a mosaic structure according to claim 1, characterized in that The heating and stirring temperature in step 5 is 70° C. to 80° C., the stirring speed is 100 r / min to 300 r / min, and the stirring time is 60 min to 75 min.

8. The method for preparing a magnetic recyclable composite photocatalyst with a mosaic structure according to claim 1, characterized in that In step 6, the time of keeping warm at 80° C. is 24 h to 36 h.

9. The method for preparing a magnetic recyclable composite photocatalyst with a mosaic structure according to claim 1, characterized in that In step 7, the temperature is kept at 180-200° C. for 60-70 minutes.

10. Use of a magnetic recyclable composite photocatalyst with a mosaic structure prepared by the preparation method according to claim 1, characterized in that A magnetic recyclable composite photocatalyst with mosaic structure for degradation of rhodamine B.